Sejarah Dakwah Sufistik KH. Abdurrahim Pasuruan Melalui Tarekat Mahabbah dalam ISHARI - Shofwan, Arif Muzayin; Hariri, Muh Mirwan (Mekomda: Media Komunikasi Dakwah, 2024)
KH. Abdurrahim Pasuruan, through the Mahabbah congregation, cannot escape the role of his grandfather, KH. Abdurrahman and studied with Habib Syaikh bin Ahmad Bafaqih Botoputih Surabaya. This qualitative descriptive writing using library research reveals KH's Sufistic preaching. Abdurrahim Pasuruan through the Mahabbah congregation. This article finds the following things, including First, the Sufistic preaching of KH. Abdurrahim Pasuruan, through the Mahabbah order, came from his father, KH. Abdul Hadi, who is named after his grandfather, KH. Abdurrahman studied with Habib Syaikh bin Ahmad Bafaqih Botoputih Surabaya. Second, during the time of KH. Abdurrahim, this Mahabbah order was formed in a forum called ISHARI which was founded on January 23, 1959. Third, the Mahabbah order in ISHARI teaches love for Allah SWT and Rasulullah SAW through reading the Book of Maulid Syaraf Al-Anam and the prayer-poems in the Book. Diwan Hadrah and several other reference books. Fourth, the Sufistic preaching of KH. Abdurrahim through the Mahabbah order in the ISHARI forum has been implemented by many Sufism experts such as Rabiah Al-Adawiyah, Ibrahim bin Adham, Sari As-Saqati, and others.